Differences in finishing actions between winning and losing teams in top-league womens´s basketball - Jørgensen, J. H. (Baltic Journal of Sport and Health Sciences, 2024)
This study aimed to identify structural differences in offensive styles between winning and losing teams in women`s basketball. The focus was on offense types, distribution, efficiency, and finishing actions. Data from 12 games in the Danish women`s 2020-21 season involving five teams were analyzed. A total of 1915 possessions were categorized into four basic offense types and 13 finishing actions using notational analysis. The findings revealed that a) losing teams utilized shots by the ball handler in pick-and-roll situations statistically significantly more; b) winning teams demonstrated significantly higher efficiency in finishing actions such as off-ball screens, cuts, isolation plays facing the basket, and miscellaneous situations; and c) in set plays, winning teams were superior in cuts and off-ball screen categories. These results accentuate differences in finishing action preferences between winning and losing teams, with winning teams showing dominant play without the ball, exemplified by the higher efficiency in cuts and off-ball categories. Understanding these differences can support coaching practices and professional strategies in women`s basketball.